2020
DOI: 10.3390/pharmaceutics12030216
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Puerarin Chitosan Oral Nanoparticles by Ionic Gelation Method and Its Related Kinetics

Abstract: In this paper, as an active ingredient, puerarin chitosan nanoparticles (Pur-CS/TPP-NPs) are prepared by an ionic gelation method. The chitosan (CS) concentration, pH of the CS solution, sodium tripolyphosphate (TPP) concentration, stirring speed, stirring time, ultrasonic power, and dosage are used as single factors for investigation, and the encapsulation efficiency, drug loading capacity, particle size, and polydispersity index (PDI) are used as indicators for investigation. The optimal prescription is dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 27 publications
(27 reference statements)
1
23
0
Order By: Relevance
“…The cellular uptake of molecules encapsulated in 200 nm chitosan nanoparticles, at 24 h, was observed in the case of the anticancer agent resveratrol [168] and BSA [3]. Similar in vivo results in a single-pass intestinal perfusion model were observed for puerarin (a molecule with bioprotective activity and obtained from a leguminous plant), which increased its bioavailability by a factor of 4.4 when encapsulated in chitosan nanoparticles [169]. Other approaches include the synthesis of thermo-responsive structures [2] and micro/nanoparticles [170,171] encapsulating the chemotherapeutic (anticancer agent) doxorubicin; and the combination of a chemotherapy (5-fluorouracil) with magnetic nanoparticles to obtain a core-shell structure for drug delivery and hyperthermia therapy [172].…”
Section: Ionotropic Gelation For the Synthesis Of Nano/microparticlessupporting
confidence: 62%
“…The cellular uptake of molecules encapsulated in 200 nm chitosan nanoparticles, at 24 h, was observed in the case of the anticancer agent resveratrol [168] and BSA [3]. Similar in vivo results in a single-pass intestinal perfusion model were observed for puerarin (a molecule with bioprotective activity and obtained from a leguminous plant), which increased its bioavailability by a factor of 4.4 when encapsulated in chitosan nanoparticles [169]. Other approaches include the synthesis of thermo-responsive structures [2] and micro/nanoparticles [170,171] encapsulating the chemotherapeutic (anticancer agent) doxorubicin; and the combination of a chemotherapy (5-fluorouracil) with magnetic nanoparticles to obtain a core-shell structure for drug delivery and hyperthermia therapy [172].…”
Section: Ionotropic Gelation For the Synthesis Of Nano/microparticlessupporting
confidence: 62%
“…The high ζ-potential of those points confirms the existence of protonated amino groups on the surface of the NPs. Moreover, increased concentration of chitosan leads in decreased intermolecular distance and increased intermolecular hydrogen bonding between the polymeric chains [ 30 , 31 , 32 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The best-known examples include SARS-CoV, MERS-CoV and SARS-CoV-2 (Chan et al, 2020), all of which pose a marked threat to human health. In addition, four other coronaviruses are known to infect humans, including HCoV-229E, HKU-NL63, HCoV-OC43 and HCoV-HKU1, which cause mild illnesses (Li et al, 2020a;Yan et al, 2020). Bats are generally thought to be the natural reservoir of a range of coronaviruses (Graham et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In early December 2019, a cluster of cases of pneumonia caused by a novel coronavirus named Sudden Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) resulted in tremendous challenges to China's public health and clinical treatment (Munster et al, 2020;Yan et al, 2020), and now it has been confirmed in more than 211 other countries and territories, causing a major global public health crisis (Day, 2020;Jernigan and Team, 2020;Peeri et al, 2020). SARS-CoV-2 belongs to the Betacoronavirus genus in the family Coronaviridae, and is closely related to severe acute respiratory syndrome coronavirus (SARS-CoV) and Middle East respiratory syndrome coronavirus (MERS-CoV) (Drosten et al, 2003;Wassenaar and Zou, 2020;Zaki et al, 2012).…”
Section: Introductionmentioning
confidence: 99%